2011
DOI: 10.1073/pnas.1107177108
|View full text |Cite
|
Sign up to set email alerts
|

Implications for the hydrologic cycle under climate change due to the expansion of bioenergy crops in the Midwestern United States

Abstract: To meet emerging bioenergy demands, significant areas of the large-scale agricultural landscape of the Midwestern United States could be converted to second generation bioenergy crops such as miscanthus and switchgrass. The high biomass productivity of bioenergy crops in a longer growing season linked tightly to water use highlight the potential for significant impact on the hydrologic cycle in the region. This issue is further exacerbated by the uncertainty in the response of the vegetation under elevated CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 40 publications
7
120
2
Order By: Relevance
“…Growing season duration has been shown to impact regional hydrology through changes in ET and drainage . Additionally, increases in LAI have been shown to increase ET (Le et al, 2011), suggesting that the relatively large and prolonged LAI of biomass sorghum could support significant ET late into the growing season. Dense crop canopies and intensely managed agroecosystems have been shown to reduce maximum summertime temperatures in the Corn Belt (i.e.…”
Section: Ruizmentioning
confidence: 99%
“…Growing season duration has been shown to impact regional hydrology through changes in ET and drainage . Additionally, increases in LAI have been shown to increase ET (Le et al, 2011), suggesting that the relatively large and prolonged LAI of biomass sorghum could support significant ET late into the growing season. Dense crop canopies and intensely managed agroecosystems have been shown to reduce maximum summertime temperatures in the Corn Belt (i.e.…”
Section: Ruizmentioning
confidence: 99%
“…At the end of the growing season, ET of corn and soybeans declines and ends a few weeks before harvest, which usually occurs at the beginning of October, but Miscanthus continues to transpire until the first frosts, usually in November (Schilling et al, 2008;McIsaac et al, 2010;Le et al, 2011), so that its growing season is two months or more longer than the current row crop annuals. In addition, the canopy of Miscanthus is much more dense than that of corn or soybeans, with a maximum leaf area index (LAI) of up to 10 compared to 7 for soybeans and 5.5 for corn (Heaton et al, 2008;Le et al, 2011) which would also intercept more water than the annual crops, thus reducing throughfall in addition to drying the soil profile earlier in the year . In a tiledrained watershed, this could mean that the local streams become baseflow-dependent earlier in the year than under row crops, and, in dry years especially, experience larger and/or longer deficit periods during the summer low flow season.…”
Section: Implications For Biofuels Land Use Changementioning
confidence: 99%
“…Both field experiments Smith et al, 2013) and watershed-scale modeling experiments (Ng et al, 2010) have shown that less nitrate is exported from Miscanthus compared to conventional corn crops. However, recent field experiments Hickman et al, 2010) and canopy-scale modeling studies (Le et al, 2011) have also shown that water usage by Miscanthus is significantly greater than that of corn or soybeans. If large-scale planting of these biomass crops is to be sustainable, it is essential to understand how watersheds as a whole might respond to this change and be aware of possible negative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Bioenergy crops, e.g., switchgrass and miscanthus, can transpire as much as 38% more than corn over a growing season [20]. Replacing traditional annual cropping systems with switchgrass in the Midwest and High Plains may cause additional stress to water resources because the agricultural crop production in large portions of these areas (e.g., Kansas and Nebraska) is dependent upon irrigation water from already stressed local resources [21].…”
Section: Introductionmentioning
confidence: 99%
“…Change in land cover thus has the potential to impact local and regional climate through alteration of the energy and moisture balances of the land surface [14][15][16][17][18]. The longer growing season and greener vegetative cover of biofuel crops result in higher water loss to the atmosphere through evapotranspiration (ET), decline in soil water depth [17,19] and reduced surface runoff [20] relative to annual cropping systems. Changes in soil moisture and runoff determine streamflow, groundwater recharge and influence water quality.…”
Section: Introductionmentioning
confidence: 99%